SEMANGAT GURU HONORER SMP KOTA SAWAHLUNTO - Dewi Marlina (Jurnal Bahana Manajemen Pendidikan, 2013)
This study is based on the existence of problems that demonstrate the spirit of part-time teachers who work less well. This study aimed to obtain information about how the junior honorary teacher morale Sawahlunto. This research is a descriptive study. The population in this study were all part-time teachers SMP Sawahlunto totaling 45 people. This study is a population study. Data collection tool used was a questionnaire or questionnaires. This questionnaire has been tested for validity and reliabelitasnya. Data were analyzed with an average score formula. In general Honorary Teacher Morale Sawahlunto SMP is in both categories with an average score overall was 3.8. Key word: Semangat